Aircraft recirculation filter for air quality and incident assessment - Eckels, Steven J.; Jones, Byron W.; Mann, Garrett W.; Mohan, Krishnan R.; Weisel, Clifford P. (My University, 2014)
The current research examines the possibility of using recirculation filters from aircraft to document the nature of air quality incidents on aircraft. These filters are highly effective at collecting solid and liquid particulates. Identification of engine oil contaminants arriving through the bleed air system on the filter was chosen as the initial focus. A two-step study was undertaken. First, a compressor/bleed air simulator (BAS) was developed to simulate an engine oil leak and samples were analyzed with gas chromatograph-mass spectrometry (GCMS). These samples provided a concrete link between tricresyl phosphates (TCPs) and a homologous series of synthetic pentaerythritol esters from oil and contaminants found on the sample paper. The second step was to test 184 used aircraft filters with the same GC-MS system: of that total, 107 were standard filters and 77 nonstandard. Four of the standard filters had both markers for oil, with the homologous series synthetic pentaerythritol esters being the less common marker. It was also found that 90% of the filters had some detectable level of TCPs. Of the 77 nonstandard filters, 30 had both markers for oil, a significantly higher percent than the standard filters.
Keywords: Recirculation filters; Aircraft; Air quality incidents